Soybean compressibility and bulk density - Milani, A. P.; Bucklin, R. A.; Teixeira, A. A.; Kebeli, H. V. (Amer Soc Agricultural Engineers, 2000)
The objective of this project was to study the influence of surcharge pressure and moisture content on the compressive behavior and bulk density of soybeans. Three varieties were selected with varying dimensions and shapes. Moisture contents of 10.5, 15.0, and 20% were tested at nine surcharge pressures in the range from 0 to 82.8 kPa. Results indicated that the bulk densities of different soybean varieties have similar behavior with respect to pressure level and moisture content but that the magnitude of bulk density was influenced by variety, Bulk density was influenced by both pressure level and moisture content. The four-element Burger model was found to adequately describe the bulk density of soybeans as a function of pressure for all varieties and moisture levels.
Keywords: bulk density; kernel density; porosity; moisture content; grain pressure; Burger model